Meningkatkan Pelayanan Publik melalui Tata Kelola Adaptif dalam Pemekaran Desa - Thahira, Shafa; Zakaria, Saifullah; Afrilia, Ufa Anita (Jurnal Governansi, 2026)
Village expansion is a decentralization strategy aimed at improving the quality of public service delivery, accelerating equitable development, and strengthening local governance. This article seeks to analyze the verification process of village expansion, identify administrative, geographical, social, and regulatory obstacles that hinder efficient public service provision, and formulate adaptive policy strategies. The study employs a qualitative descriptive-analytical approach, based on field observations during an internship at the Directorate General of Village Government under the Ministry of Home Affairs, document analysis of regulations such as Law No. 6 of 2014, Government Regulation No. 78 of 2007, and Ministerial Regulation No. 1 of 2017, as well as a review of 25 recent academic journals and policy reports. The findings reveal that in underdeveloped, frontier, and outermost (3T) regions like Pegunungan Arfak, 63% of village expansion proposals were returned due to formatting errors, non-digital maps, and incomplete deliberation documentation. Extreme topography delayed on-site verification and increased operational costs, while overlapping regulations and limited human resource capacity negatively impacted post-expansion public service effectiveness. A SWOT-based strategy was developed, including map digitalization, delegation of initial verification authority to the provincial level, technical training for village officials, and harmonization of national-local regulatory frameworks. This article is expected to contribute both conceptually and practically to the development of village expansion governance that is responsive to public service needs and sustainable in remote areas.